2016
DOI: 10.14260/jemds/2016/1210
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pranayama on Blood Pressure and Heart Rate in Premenstrual Syndrome

Abstract: Premenstrual syndrome (PMS) also called PMT or premenstrual tension refers to the cyclic recurrence of a combination of distressing physical, psychological or behavioural changes, during the luteal phase of the menstrual cycle. It is suggested that there is altered autonomic activity in the late luteal phase of their endometrial cycle. Practice of breathing exercises like pranayama is known to improve autonomic function by changing sympathetic or parasympathetic activity. AIMThe aim of study was to investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
(10 reference statements)
1
0
0
Order By: Relevance
“…These results indicated the favorable effect of breathing exercises with or without walking program on decreasing resting HR in females having PMS. These results are consistent with studies that found a significant reduction in HR in PMS females after 3 months of breathing exercises practice in the form of pranayama (30,31). Females with PMS have sympathovagal imbalance with shifting of autonomic balance in favor of sympathetic activity and these females are unable to cope up with stressful situations.…”
Section: Discussionsupporting
confidence: 92%
“…These results indicated the favorable effect of breathing exercises with or without walking program on decreasing resting HR in females having PMS. These results are consistent with studies that found a significant reduction in HR in PMS females after 3 months of breathing exercises practice in the form of pranayama (30,31). Females with PMS have sympathovagal imbalance with shifting of autonomic balance in favor of sympathetic activity and these females are unable to cope up with stressful situations.…”
Section: Discussionsupporting
confidence: 92%